The way from pen and paper to electronic documentation in a German emergency department - Benjamin Lucas (BMC Health Services Research, 2019)
Abstract Background Some of the advantages of implementing electronic emergency department information systems (EDIS) are improvements in data availability and simplification of statistical evaluations of emergency department (ED) treatments. However, for multi-center evaluations, standardized documentation is necessary. The AKTIN project (“National Emergency Department Register: Improvement of Health Services Research in Acute Medicine in Germany”) has used the “German Emergency Department Medical Record” (GEDMR) published by the German Interdisciplinary Association of Intensive and Emergency Care as the documentation standard for its national data registry. Methods Until March 2016 the documentation standard in ED was the pen-and-paper version of the GEDMR. In April 2016 we implemented the GEDMR in a timeline-based EDIS. Related to this, we compared the availability of structured treatment information of traumatological patients between pen-and-paper-based and electronic documentation, with special focus on the treatment time. Results All 796 data fields of the 6 modules (basic data, severe trauma, patient surveillance, anesthesia, council, neurology) were adapted for use with the existing EDIS configuration by a physician working regularly in the ED. Electronic implementation increased availability of structured anamnesis and treatment information. However, treatment time was increased in electronic documentation both immediately (2:12 ± 0:04 h; n = 2907) and 6 months after implementation (2:18 ± 0:03 h; n = 4778) compared to the pen-and-paper group (1:43 ± 0:02 h; n = 2523; p < 0.001). Conclusions We successfully implemented standardized documentation in an EDIS. The availability of structured treatment information was improved, but treatment time was also increased. Thus, further work is necessary to improve input time.